2016
DOI: 10.3920/cep150029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of minimalist, maximalist and energy return footwear of equal mass on running economy and substrate utilisation

Abstract: (2016) The effect of minimalist, maximalist and energy return footwear of equal mass on running economy and substrate utilization. Equine and Comparative Exercise Physiology, 12 (1). pp. 4954. ISSN 17552540It is advisable to refer to the publisher's version if you intend to cite from the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…The current study showed firstly that the energy return shoes were associated with significantly reduced net VO 2 in comparison to the conventional and spring footwear, indicating that economy was enhanced in this condition. This observation supports the findings of Sinclair et al (2015) and Sinclair et al (2016) who showed that the energy boost footwear were most economical in relation to conventional, minimalist and maximalist shoe conditions. Given the proposed association between running economy and performance, this indicates that the energy return footwear may be associated with increased performance in relation to the conventional and spring footwear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study showed firstly that the energy return shoes were associated with significantly reduced net VO 2 in comparison to the conventional and spring footwear, indicating that economy was enhanced in this condition. This observation supports the findings of Sinclair et al (2015) and Sinclair et al (2016) who showed that the energy boost footwear were most economical in relation to conventional, minimalist and maximalist shoe conditions. Given the proposed association between running economy and performance, this indicates that the energy return footwear may be associated with increased performance in relation to the conventional and spring footwear.…”
Section: Discussionsupporting
confidence: 91%
“…Sinclair et al (2015) demonstrated that the energy return footwear significantly improved running economy in comparison to a conventional running shoe. In addition, Sinclair et al (2016) showed that energy return shoes improved running economy and reduced the bodies reliance on carbohydrate as an energy source in comparison to minimalist and maximalist footwear of equal mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote running performance, some footwear technologies have recently been introduced into running shoes (Sinclair, Shore, & Dillon, 2016). Among them, a newly developed design, called "actuator lugs," which embedded under minimalist shoes (Newton Running Lab®, Boulder, CO, USA), claims for better shock absorption and energy return (Abshire, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Energy return has become a contemporary topic in footwear biomechanics literature [17][18][19]. The first energy return footwear utilized a thermoplastic polyurethane midsole which is designed to reduce energy loss in comparison to traditional ethylene-vinyl acetate footwear midsoles.…”
Section: Introductionmentioning
confidence: 99%